The Museum as a Product Provider: the Impact of Its Emotional Intelligence on Customer Satisfaction - Miežietytė-Gudzinskė, Alina; Jurėnienė, Virginija (Vilnius University Open Series, 2022)
Growing competition in the field of culture, the need to compete in the leisure entertainment market forces museums to adapt to new conditions and rethink the structure of the institution, how exhibitions are created and presented, and other accompanying programs services. Meanwhile, museums still lack visitor satisfaction surveys, they are rarely conducted, and questionnaires help to understand the sociodemographic and social aspects of the audience but do not help the museum to find out what the visitor expected and whether the services met their expectations. Therefore, to stay creative and competitive in the marketplace, museums must consider the needs of their visitors, but at the same time keep in mind their emotional intelligence as a product and service provider. The organization’s emotional intelligence is a very important factor that can affect visitor satisfaction. The emotional intelligence of the museum employees has not yet been studied in museums with the aim of calculating whether it can correlate with visitor satisfaction with the museum. All research conducted so far has analyzed visitor satisfaction but did not consider museum staff as the most important link in the process.